MANAJEMEN RISIKO (PROTEKSI) ASET KLIEN BAPAK RUSDIANSYAH STUDI KASUS WEALTH MANAGEMENT - , Widya Nurshanty ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims at identifying individual investment risk profile included into a âHigh Networth Individualsâ category. After recognizing the investment risk profile, an evaluation is done to find out whether or not the investment has been in accordance with the investment risk profile. The study also aims at finding out whether or not the assets have protection. If no protection, it is recommended that the assets are protected by assurance in accordance with the profile of investment risk today. The case study was conducted by involving a client who is willing to be an informant and provide information about data on personal wealth stated in balance sheet, income and expenditure stated in cash flow, and other information related to the management of assets owned by the client. The investment risk profile was based on questionnaire completed by the client. Based on the profile, the researcher then given recommendation in accordance with the clientâs need, i.e. the protection of assets as well as the optimization of income by utilizing the property the client owned in order to be more productive. Results of the measurement of investment risk profile, it can be concluded that the client was a type of individual who takes a relatively conservative risk, while at present he has no protection over his assets. Therefore, a recommendation is given that he should provide the protection on his assets, so the risk possibly occur to the assets can be assured by other party, in accordance with his investment risk profile, i.e. he is a relatively conservative people or tends to avoid risk. For the protection of vehicle and burn, he used the assurance from ASRI ACA, while for life and health assurances he used the assurance from BNI Life. In addition, results of the evaluation show that the risk and investment profiles have at present matched. The optimization of the clientâs income was carried out by subtracting the amount of work capital credit, changing the type of saving and a period of time for deposito, renting out some properties such as house and two cars, and trying a new business, i.e. the cultivation of Emprit ginger. Based on the recommendation, it can be calculated that the investment can increase income surplus for the client from IDR 249,519,808 to IDR 447,040,052 or increased for IDR 197,520,244.